2013
DOI: 10.1038/hdy.2013.104
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic and population genetic analyses reveal Pleistocene isolation followed by high gene flow in a wide ranging, but endangered, freshwater mussel

Abstract: Freshwater organisms of North America have had their contemporary genetic structure shaped by vicariant events, especially Pleistocene glaciations. Life history traits promoting dispersal and gene flow continue to shape population genetic structure. Cumberlandia monodonta, a widespread but imperiled (IUCN listed as endangered) freshwater mussel, was examined to determine genetic diversity and population genetic structure throughout its range. Mitochondrial DNA sequences and microsatellite loci were used to mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 51 publications
5
49
1
1
Order By: Relevance
“…We followed procedures for conditions for PCR, sequencing and post‐sequencing analyses described in Inoue et al . ().…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…We followed procedures for conditions for PCR, sequencing and post‐sequencing analyses described in Inoue et al . ().…”
Section: Methodsmentioning
confidence: 97%
“…We used previously published procedures for fragment analyses, allele scoring and assignment of integer numbers to DNA fragment sizes (Inoue et al . ).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Those authors raised the possibility that observed species differences in gene flow between rivers was due to differences in host vagility (different mussel species utilizing different fish species as hosts), but such and explanation is not valid in this case as both mussels share the same host fish. Inoue et al (2013) noted that since freshwater mussels and their hosts live in linear river systems, mussels with vagile hosts can be dispersed across great distances which would results in low or no population differentiation. Aplodinotus grunniens, like brown trout, has higher mobility than does the common logperch.…”
mentioning
confidence: 99%